4a+6=6a-6

Simple and best practice solution for 4a+6=6a-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a+6=6a-6 equation:


Simplifying
4a + 6 = 6a + -6

Reorder the terms:
6 + 4a = 6a + -6

Reorder the terms:
6 + 4a = -6 + 6a

Solving
6 + 4a = -6 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
6 + 4a + -6a = -6 + 6a + -6a

Combine like terms: 4a + -6a = -2a
6 + -2a = -6 + 6a + -6a

Combine like terms: 6a + -6a = 0
6 + -2a = -6 + 0
6 + -2a = -6

Add '-6' to each side of the equation.
6 + -6 + -2a = -6 + -6

Combine like terms: 6 + -6 = 0
0 + -2a = -6 + -6
-2a = -6 + -6

Combine like terms: -6 + -6 = -12
-2a = -12

Divide each side by '-2'.
a = 6

Simplifying
a = 6

See similar equations:

| .5x+8=.25x-10 | | 3(41-7)= | | 9y-9-7y+6=0 | | 4-3x+13=23 | | -6y+20-y=-3y+9 | | 3x+4x(2+7)=72 | | 2x^2-3x+2=17 | | 35x+45=40x | | 6x-7y-11x+y=2x+6 | | 1.25x=7.5 | | (3x+143)=(2x+27) | | x^2=5x-66 | | 0.25n=6.25 | | 4x-7=24x+8 | | 4.5x+31.5=0 | | =11+3(b+5) | | 4x-10=-5x-10 | | 3-8x+2x=18 | | 3+12z=21 | | 4x+12y-3=0 | | (2x^2+5y+3)-(8y-6x+5)= | | 4x=5(x-8) | | 4-2=3(t-1)-5 | | -5(r+3)=-81 | | 14m-3=7m+6-2n | | 15(X)(X+2)=2145 | | 4(-9)-70= | | 2x-6=x-3(2-x) | | -7-x=x-9 | | 44-7p=30 | | 4x-9-70= | | 7(2a+1)=14p+7 |

Equations solver categories